A method for in-situ growth of zinc salts of variable valence metal acids to protect zinc negative electrodes
By growing the zinc salt protective layer of variable valence metallic acid in situ on the surface of the zinc negative electrode, the problem of uneven growth and deposition of zinc dendrites in zinc ion batteries is solved, and the stability and performance of zinc ion batteries are significantly improved, which has promoted its large-scale application.
Patent Information
- Application Number
- CN202311262945.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-09-27
AI Technical Summary
There are problems in aqueous zinc ion batteries that have zinc dendrites that are not uniform in growth, deposition, slow kinetics and corrosion, which affect their performance and cycle life and limit their large-scale application.
Prepare a protective layer of zinc salt in situ on the surface of zinc negative electrode. By dissolving zinc salt and variable metal salt, it forms a crystal core of zinc salt in value, and grows a protective layer in situ on the surface of zinc foil to promote uniform deposition of zinc ions and Dynamics accelerate.
The uniform deposition of zinc negative electrode is achieved, the growth of zinc dendrites is inhibited, the zinc ion deposition kinetics is improved, the cycle life is increased, and the polarization voltage is reduced, which significantly improves the stability and performance of aqueous zinc batteries.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry, and in particular relates to a method for in-situ growth preparation of a zinc negative electrode protected by a variable-valence metal acid zinc salt. Background Art
[0002] Recently, many countries and regions have increased their investment in renewable energy, so the research and production of green and efficient chemical batteries has become a hot topic. Among various energy storage systems, lithium-ion batteries are currently the most widely used rechargeable electrochemical devices. In the past nearly three decades, lithium-ion batteries have occupied a major position in new energy electric vehicles and various electronic devices. However, due to the flammable organic electrolytes and the high activity of lithium substances, lithium-ion batteries have certain hidden dangers, such as potential safety issues. In addition, the high cost and abundance of lithium resources on the earth limit the long-term development of lithium-ion batteries.
[0003] In this context, researchers began to look for new energy storage solutions that can replace lithium-ion batteries, including sodium-ion batteries, magnesium-ion batteries, and aluminum-ion batteries. In contrast, aqueous metal-ion batteries using multivalent charge carriers seem to attract more attention. Compared with traditional organic electrolyte-based lithium-ion batteries, metal-ion batteries with aqueous solutions as electrolytes have the advantages of better safety performance, ultra-high ionic conductivity, simple preparation process and lower cost. Therefore, they are expected to replace lithium-ion batteries and achieve large-scale applications. At present, many types of aqueous metal-ion batteries have been developed, such as zinc-based batteries, sodium-ion batteries, potassium-ion batteries, aluminum-ion batteries, magnesium-ion batteries, and calcium-ion batteries. Compared with other active metals, zinc metal has a more suitable redox potential (-0.76 V vs. standard hydrogen electrode) and excellent Zn / Zn in aqueous electrolytes. 2+ Reversible, can be used directly as negative electrode. In addition, zinc metal is abundant in nature, making the procurement and processing costs of zinc low. More importantly, the zinc negative electrode also has a very high theoretical capacity (820mAh g -1 and 5854 mAh cm -3), therefore, aqueous zinc-ion batteries have attracted enough attention. However, although zinc negative electrodes have many natural advantages, and people are also committed to designing and developing high-performance positive electrodes and aqueous electrolytes for zinc-ion batteries, there are still some thorny problems in aqueous zinc-ion batteries, such as hydrogen evolution reaction, positive electrode dissolution, water evaporation, zinc dendrite generation, corrosion and liquid leakage, etc. These problems may have a huge impact on its performance, resulting in reduced coulombic efficiency, capacity attenuation and short circuit of aqueous zinc-ion batteries, which seriously affects the large-scale application of zinc-ion batteries and greatly limits the development and industrialization of aqueous zinc-ion batteries. Therefore, in the face of these existing problems and challenges, it is very necessary to propose appropriate treatment plans in a timely manner.
[0004] At present, researchers mainly prepare the zinc negative electrode of new aqueous zinc ion batteries from the aspects of eliminating zinc dendrites, changing hydrogen evolution potential and improving corrosion resistance. In recent years, important progress has been made in the optimization of zinc negative electrodes for aqueous zinc ion batteries, which can be mainly divided into three-dimensional structure design, electrolyte optimization, interface coating construction and diaphragm modification. Among the many zinc negative electrode optimization strategies, artificial interface coating construction has the advantages of inhibiting zinc dendrite growth and avoiding side reactions, and is considered to be one of the ideal choices for solving many problems of zinc metal negative electrodes. However, the artificial protective layer obtained by the non-in-situ coating method is usually uneven and cannot effectively prevent the electrolyte from reaching the surface of the zinc negative electrode, resulting in slow zinc ion deposition kinetics. In addition, this type of protective layer has poor zinc surface adhesion and is very easy to fall off and break due to volume changes during the cycle, resulting in the failure of the protective effect. Therefore, it is very meaningful to develop a protective layer that is uniformly distributed, can form an in-situ interface with strong adhesion to zinc, and can accelerate the zinc ion deposition kinetics.
[0005] In view of the above problems, the present invention in situ prepares a uniform interfacial coating of a variable valence metal acid zinc salt on the surface of the zinc negative electrode. Due to the variable valence metal acid zinc salt protective layer grown in situ on the surface of the zinc negative electrode, the metal acid radicals therein can react with the solvated [Zn(H 2 O) 6 ] 2+ H in ions 2 O combination, promoting [Zn(H 2 O) 6 ] 2+ The desolvation process of ions can achieve uniform deposition of zinc negative electrode and inhibit the growth of zinc dendrites. At the same time, due to the participation of variable-valence metal acid radicals in the deposition of zinc ions, the change in the valence of the variable-valence metal can promote the acceleration of zinc ion deposition kinetics. Therefore, the variable-valence metal acid zinc salt @ Zn negative electrode exhibits a long cycle life and a small polarization voltage, indicating that it has great potential as a highly stable negative electrode for aqueous zinc ion batteries. Summary of the invention
[0006] In view of the above problems, the present invention provides a method for in-situ growth of a variable-valence metal acid zinc salt to protect a zinc negative electrode. The protective layer of the variable-valence metal acid zinc salt can promote uniform zinc deposition, solve the problem of uneven zinc deposition causing zinc dendrites and slow zinc deposition kinetics, thereby achieving the purpose of inhibiting the growth of dendrites and accelerating the zinc ion deposition kinetics.
[0007] The technical means adopted by the present invention are as follows:
[0008] A method for in-situ growth of a zinc salt of a variable valence metal acid to protect a zinc negative electrode, comprising the following steps:
[0009] S1. Preparation of variable valence metal acid zinc salt: dissolving zinc salt and variable valence metal salt into deionized water solution to obtain zinc salt solution and variable valence metal salt solution respectively, mixing the zinc salt solution and the variable valence metal salt solution, and generating variable valence metal acid zinc salt crystal nuclei in the solution.
[0010] The zinc salt is zinc acetate, zinc chloride, zinc sulfate, zinc nitrate, zinc perchlorate or zinc trifluoromethanesulfonate, and the concentration of the zinc salt solution is 1-1000 mM. The variable valence metal salt is sodium titanate, sodium chromate, sodium cobaltate, sodium zirconate or sodium tungstate, and the concentration of the variable valence metal salt solution is 1-1000 mM; the generated variable valence metal acid zinc salt is zinc titanate, zinc chromate, zinc ferrite, zinc cobaltate, zinc zirconate or zinc tungstate.
[0011] S2. In-situ growth of variable-valence metal acid zinc salt: zinc foil is placed in a solution for generating variable-valence metal acid zinc salt. There is a deposition-dissolution equilibrium between the zinc foil and the solution. After 1-60 minutes, a protective layer of variable-valence metal acid zinc salt is generated in-situ on the surface of the zinc foil to obtain a variable-valence metal acid zinc salt-protected zinc negative electrode (variable-valence metal acid zinc salt@Zn electrode).
[0012] The thickness of the variable valence metal acid salt protective layer increases with the reaction time. In order to ensure that the ion transmission in the electrolyte of the ideal metal acid zinc salt protective layer is not hindered, the thickness of the in-situ growth needs to be controlled within 1-100 μm.
[0013] The metal acid radicals in the variable valence metal acid salt protective layer can react with the solvated [Zn(H 2 O) 6 ] 2+ H in ions 2 O combination, promoting [Zn(H 2 O) 6 ] 2+The desolvation process of ions can achieve the purpose of uniform deposition of zinc negative electrode and inhibit the growth of zinc dendrites. In the process of zinc ion deposition, the variable valence metal acid salt protective layer participates in the variable valence metal acid radical. The change of the valence of the variable valence metal can promote the acceleration of zinc ion deposition kinetics, thereby improving the performance of aqueous zinc batteries.
[0014] S3. Assembly of zinc-based batteries: The variable-valent metal acid zinc salt @Zn electrode is taken out, rinsed with deionized water and dried, used as the negative electrode of the zinc battery, and assembled into a battery with an aqueous electrolyte.
[0015] The aqueous electrolyte is a zinc sulfate solution, a zinc acetate solution, a tetrahydroxy zinc solution, a zinc trifluoromethanesulfonate solution, a zinc chloride solution or a zinc nitrate solution, and its concentration is 0.2-3M.
[0016] Compared with the prior art, the method for in-situ growth of a variable-valence metal acid zinc salt to protect a zinc negative electrode has the following beneficial effects:
[0017] , the method for in-situ growth of preparing variable-valence metal acid zinc salt to protect zinc negative electrode in the present invention has uniform in-situ growth interface and strong adhesion.
[0018] The method for in-situ growth of a variable valence metal acid zinc salt to protect a zinc negative electrode of the present invention, wherein the metal acid radical can react with the solvated [Zn(H 2 O) 6 ] 2+ H in ions 2 O combination, promoting [Zn(H 2 O) 6 ] 2+ The desolvation process of ions can achieve uniform deposition of zinc negative electrode and inhibit the growth of zinc dendrites.
[0019] 2. The method of in-situ growth of a variable-valence metal acid zinc salt to protect a zinc negative electrode in the present invention, during the zinc ion deposition process, due to the participation of the variable-valence metal acid radical, the change in the valence of the variable-valence metal can promote the acceleration of the zinc ion deposition kinetics, thereby improving the performance of the aqueous zinc battery.
[0020] The present invention can be carried out at room temperature, does not require complicated equipment and cumbersome processing procedures, is simple to operate, energy-saving and environmentally friendly, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 (a) is 1 mA cm in Example 1 of the present invention. -2 The charge and discharge curves of zinc tungstate protected zinc foil at a current density of; Figure 1(b) is 1 mA cm in Comparative Example 1 of the present invention -2 Charge and discharge curves of pure bare zinc at a current density of .
[0022] Figure 2 (a) is 3 mA cm in Example 1 of the present invention. -2 The charge and discharge curves of zinc tungstate protected zinc foil at a current density of; Figure 2 (b) is 3 mA cm in Comparative Example 1 of the present invention -2 Charge and discharge curves of pure bare zinc at a current density of .
[0023] Figure 3 (a) is 5 mA cm in Example 1 of the present invention. -2 The charge and discharge curves of zinc tungstate protected zinc foil at a current density of; Figure 3 (b) is 5 mA cm in Comparative Example 1 of the present invention -2 Charge and discharge curves of pure bare zinc at a current density of .
[0024] Figure 4 (a) is 1 mA cm in Example 2 of the present invention. -2 The charge and discharge curves of zinc foil protected by zinc chromate at a current density of; Figure 4 (b) is 1 mA cm in Comparative Example 1 of the present invention -2 Charge and discharge curves of pure bare zinc at a current density of .
[0025] Figure 5 (a) is 3 mA cm in Example 2 of the present invention. -2 The charge and discharge curves of zinc foil protected by zinc chromate at a current density of; Figure 5 (b) is 3 mA cm in Comparative Example 1 of the present invention -2 Charge and discharge curves of pure bare zinc at a current density of .
[0026] Figure 6 (a) is 5 mA cm in Example 2 of the present invention. -2 The charge and discharge curves of zinc foil protected by zinc chromate at a current density of; Figure 6 (b) is 5 mA cm in Comparative Example 1 of the present invention -2 Charge and discharge curves of pure bare zinc at a current density of .
[0027] Figure 7 (a) is 1 mA cm in Example 3 of the present invention. -2 The charge and discharge curves of zinc titanate protected zinc foil at a current density of; Figure 7 (b) is 1 mA cm in Comparative Example 1 of the present invention -2 Charge and discharge curves of pure bare zinc at a current density of .
[0028] Figure 8 (a) is 3 mA cm in Example 3 of the present invention. -2 The charge and discharge curves of zinc titanate protected zinc foil at a current density of; Figure 8 (b) is 3 mA cm in Comparative Example 1 of the present invention -2 Charge and discharge curves of pure bare zinc at a current density of .
[0029] Fig. 9 (a) is 5 mA cm in Example 3 of the present invention. -2 The charge and discharge curves of zinc titanate protected zinc foil at a current density of; Fig. 9 (b) is 5 mA cm in Comparative Example 1 of the present invention -2 Charge and discharge curves of pure bare zinc at a current density of . DETAILED DESCRIPTION
[0030] The following is a detailed description through specific implementation methods.
[0031] Example 1
[0032] S1. Preparation of zinc tungstate: Dissolve zinc sulfate and sodium tungstate in deionized water to obtain a 5 mM zinc sulfate solution and a 5 mM sodium tungstate solution, respectively. Mix 10 mL of the zinc sulfate solution and 10 mL of the sodium tungstate solution to generate zinc tungstate crystal nuclei in the solution.
[0033] S2. In-situ growth of zinc tungstate: A piece of pre-cleaned zinc foil is placed in a solution for generating zinc tungstate crystal nuclei. There is a deposition-dissolution equilibrium between the zinc foil and the solution. After 3 minutes, a protective layer of zinc tungstate is generated in-situ on the surface of the zinc foil.
[0034] S3. Assembly of zinc-based battery: The zinc tungstate @Zn electrode is taken out, rinsed with deionized water and dried, used as the negative electrode of the zinc battery, and assembled with an aqueous electrolyte. The aqueous electrolyte is an aqueous solution of zinc sulfate. Figure 1 a, 2a, and 3a are the charge and discharge curves of zinc tungstate protected zinc foil at different current densities. Figure 1 a, 3a, and 5a show that when the current density is 1 mA cm -2 , 3 mA cm -2 , 5mA cm -2 The deposition surface capacity is 1 mAh cm -2 When the polarization voltage of the metal negative electrode zinc foil is 26.6, 38.52, and 49.79 mV, respectively. Figure 1 The polarization voltage of the comparative example 1 of b, 2b, and 3b is significantly reduced, and it can be seen that after a period of charge and discharge, Figure 1The polarization voltages of a, 2a, and 3a are very stable, indicating that the interface layer accelerates the kinetics of zinc ion deposition and dissolution. The electrochemically stable zinc tungstate@Zn interface layer acts as an ion sieve, making Zn 2+ Ions are uniformly plated / stripped while water molecules and anions are repelled, improving the cycling stability of zinc batteries.
[0035] Example 2
[0036] S1. Preparation of zinc chromate: Dissolve zinc sulfate and sodium chromate in deionized water to obtain a 5 mM zinc sulfate solution and a 5 mM sodium chromate solution, respectively; mix 10 mL of the zinc sulfate solution and 10 mL of the sodium chromate solution to generate zinc tungstate crystal nuclei in the solution.
[0037] S2. In-situ growth of zinc chromate: A piece of pre-cleaned zinc foil is placed in a solution for generating zinc tungstate nuclei. There is a deposition-dissolution equilibrium between the zinc foil and the solution. After 3 minutes, a protective layer of zinc chromate is generated in-situ on the surface of the zinc foil.
[0038] S3. Assembly of zinc-based battery: The zinc chromate@Zn electrode is taken out, rinsed with deionized water and dried, and used as the negative electrode of the zinc battery. The battery is assembled with an aqueous electrolyte. The aqueous electrolyte is an aqueous solution of zinc sulfate. Figure 4 a, 5a, and 6a are the charge and discharge curves of zinc foil protected by zinc chromate at different current densities. Figure 4 a, 5a, and 6a show that when the current density is 1 mA cm -2 , 3 mA cm -2 , 5mA cm -2 The deposition surface capacity is 1 mAh cm -2 When the polarization voltage of the metal negative electrode zinc foil is 34.32, 36.1, and 45.46 mV, respectively. Figure 4 The polarization voltage of the comparative example 1 of b, 5b, and 6b is significantly reduced, and it can be seen that after a period of charge and discharge, Figure 4 The polarization voltages of a, 5a, and 6a are very stable, indicating that the interface layer accelerates the kinetics of zinc ion deposition and dissolution. The electrochemically stable zinc chromate@Zn interface layer acts as an ion sieve, making Zn 2+ Ions are uniformly plated / stripped while water molecules and anions are repelled, improving the cycling stability of zinc batteries.
[0039] Example 3
[0040] S1. Preparation of zinc titanate: zinc sulfate and sodium titanate are dissolved in deionized water respectively to obtain a 5 mM zinc sulfate solution and a 5 mM sodium titanate solution, 10 mL of the zinc sulfate solution and 10 mL of the sodium titanate solution are mixed to generate zinc titanate crystal nuclei in the solution.
[0041] S2. In-situ growth of zinc titanate: A piece of pre-cleaned zinc foil is placed in a solution for generating zinc titanate crystal nuclei. There is a deposition-dissolution equilibrium between the zinc foil and the solution. After 3 minutes, a protective layer of zinc titanate is generated in-situ on the surface of the zinc foil.
[0042] S3. Assembly of zinc-based battery: The zinc titanate@Zn electrode is taken out, rinsed with deionized water and dried, used as the negative electrode of the zinc battery, and assembled into a battery with an aqueous electrolyte. The aqueous electrolyte is an aqueous solution of zinc sulfate. Figure 7 a, 8a, and 9a are the charge and discharge curves of zinc titanate protected zinc foil at different current densities. Figure 7 a, 8a, and 9a show that when the current density is 1 mA cm -2 , 3 mA cm -2 , 5mA cm -2 The deposition surface capacity is 1 mAh cm -2 When the polarization voltage of the metal negative electrode zinc foil is 29.57, 34.52, and 54.5 mV, respectively. Figure 7 The polarization voltage of the comparative example 1 of b, 8b, and 9b is significantly reduced, and it can be seen that after a period of charge and discharge, Figure 7 The polarization voltages of a, 8a, and 9a are very stable, indicating that the interface layer accelerates the kinetics of zinc ion deposition and dissolution. The electrochemically stable zinc titanate@Zn interface layer acts as an ion sieve, making Zn 2+ Uniform ion plating / stripping, while repelling water molecules and anions, improves the cycling stability of zinc batteries
[0043] Comparative Example 1
[0044] S1: At room temperature, use fine sandpaper to polish the metal negative electrode zinc foil to remove the zinc oxide on its surface, and then wash and dry it to obtain a bare zinc electrode.
[0045] S2: Pure bare zinc was selected as the electrode material, glass fiber as the separator, and zinc sulfate solution as the electrolyte to assemble a button-type symmetrical battery for electrochemical performance testing. Under the same test conditions, the charge and discharge curves of pure bare zinc were tested. It can be seen that at 1 mA cm -2 , 3 mA cm -2 , 5mA cm -2 The polarization voltages at the current density are 46.98, 78.32, and 89.6 mV, respectively. From the charge and discharge curves of pure bare zinc, it can be seen that the unprotected zinc negative electrode material has poor stability and slow kinetic behavior, while the variable valence metal acid zinc salt negative electrode material has a smaller overpotential difference and polarization voltage, indicating that the interface layer acts as an ion sieve, making Zn 2+ Ions are uniformly plated / stripped while water molecules and anions are repelled, improving the cycling stability of zinc batteries.
[0046] The embodiments described above are merely descriptions of preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for in-situ growth of a zinc salt of a variable valence metal acid to protect a zinc negative electrode, comprising the following steps: S1. Preparation of variable valence metal acid zinc salt: dissolving a zinc salt and a variable valence metal salt into a deionized water solution to obtain a zinc salt solution and a variable valence metal salt solution, respectively; mixing the zinc salt solution and the variable valence metal salt solution, and generating variable valence metal acid zinc salt crystal nuclei in the solution; the zinc salt is zinc acetate, zinc chloride, zinc sulfate, zinc nitrate, zinc perchlorate or zinc trifluoromethanesulfonate, and the concentration of the zinc salt solution is 5 mM; the variable valence metal salt is sodium titanate, sodium chromate, sodium cobaltate, sodium zirconate or sodium tungstate, and the concentration of the variable valence metal salt solution is 5 mM; the generated variable valence metal acid zinc salt is zinc titanate, zinc chromate, zinc cobaltate, zinc zirconate or zinc tungstate; S2. In-situ growth of variable-valence metal acid zinc salt: zinc foil is placed in a solution for generating variable-valence metal acid zinc salt. There is a deposition-dissolution equilibrium between the zinc foil and the solution. After 3 minutes, a protective layer of variable-valence metal acid zinc salt is in-situ generated on the surface of the zinc foil to obtain a variable-valence metal acid zinc salt-protected zinc negative electrode. The thickness of the in-situ grown protective layer of the variable-valence metal acid zinc salt is controlled to be 1-100 μm.
Citation Information
Patent Citations
In-situ preparation method of solid electrolyte interface for negative electrode of zinc battery
CN114597482A